1994
DOI: 10.1007/bf00024530
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for nitrate content between cultivars of endive (Cichorium endiviae L.)

Abstract: A high nitrate content is a negative quality trait in vegetables . Endive (Cichorium endiviae L .) contributes considerably to human nitrate intake in Northwestern Europe . A collection of 125 commercially available cultivars of endive were grown on nutrient solution and evaluated for genetic variation between cultivars for the nitrate concentration in expressed sap . In two subsequent experiments 23 cultivars, representing the range of nitrate levels found in the first experiment, were grown both in soil and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…The minimum level of nitrate present in the NH 4 + -N treatment was probably due to the mixed N nutrition supplied before the beginning of the treatments. Ammonium nutrition could represent an agronomic strategy to reduce nitrate accumulation in the edible portion of vegetables (Santamaria et al, 1998), especially if few genotypic differences existed in the species (Reinink et al, 1994). In fact, in the nitrate-fed plants, the difference in nitrate content between 'Pancalieri Castello' and 'Nepal' was limited (Table IV).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The minimum level of nitrate present in the NH 4 + -N treatment was probably due to the mixed N nutrition supplied before the beginning of the treatments. Ammonium nutrition could represent an agronomic strategy to reduce nitrate accumulation in the edible portion of vegetables (Santamaria et al, 1998), especially if few genotypic differences existed in the species (Reinink et al, 1994). In fact, in the nitrate-fed plants, the difference in nitrate content between 'Pancalieri Castello' and 'Nepal' was limited (Table IV).…”
Section: Discussionmentioning
confidence: 95%
“…Endive is classified among the "high nitrate content" vegetables, and can accumulate up to 2,500 mg kg -1 FW of this ion (Santamaria, 2006). The chances of achieving a substantial reduction in nitrate level by cultivar choice and/or breeding are probably low (Reinink et al, 1994). N nutrition and light intensity have been identified as the major factors that influence nitrate accumulation in vegetables.…”
mentioning
confidence: 99%
“…It has been demonstrated that nitrate ions are involved in osmoregulation in plants [6]. In the studies conducted by C a r d e n a s -N a v a r r o et al [7], a highly significant positive correlation between nitrate and water content in tomato plants was noted. According to some researchers, nitrate content is under genetic control and can vary between species or even cultivars [8]. Nevertheless, this problem remains unsolved for numerous species.…”
Section: Introductionmentioning
confidence: 99%
“…Pak-choi is one of the main leafy vegetables cultivated year-round. NO 3 − is part of the nitrogen (N) cycle in nature (Santamaria, 2006), and its accumulation in plants differs among types and varieties owing to genetics (Martignon et al, 1994;Reinink et al, 1994). The accumulation of NO 3 − is most obvious in leafy vegetables such as lettuce, spinach, celery, and Pak-choi.…”
Section: Introductionmentioning
confidence: 99%